2021
DOI: 10.1007/s00431-021-04339-x
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatremia at the onset of necrotizing enterocolitis is associated with intestinal surgery and higher mortality

Abstract: It has previously been shown that hyponatremia reflects the severity of inflammation in pediatric gastrointestinal diseases. Interpretation of electrolyte disorders is a common, but not well studied challenge in neonatology, especially in the context of early detection of necrotizing enterocolitis and bowel necrosis. The aim of this study was to assess if hyponatremia, or a decrease in plasma sodium level, at the onset of necrotizing enterocolitis (NEC) is associated with intestinal ischemia/necrosis requiring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…The most common cause of euvolemic hyponatremia is the syndrome of inappropriate antidiuretic hormone (SIADH) secretion, which can be significantly exacerbated by systemic inflammation. Additionally, CRP is associated with hyponatremia (Park and Shin, 2013;Baez et al, 2023). This infant exhibited elevated white blood cell count and CRP, indicating the presence of an infection-related inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…The most common cause of euvolemic hyponatremia is the syndrome of inappropriate antidiuretic hormone (SIADH) secretion, which can be significantly exacerbated by systemic inflammation. Additionally, CRP is associated with hyponatremia (Park and Shin, 2013;Baez et al, 2023). This infant exhibited elevated white blood cell count and CRP, indicating the presence of an infection-related inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“… 7 13 Interpretation of electrolyte disorders should be given more attention. 13 WBC, CRP, PCT, and IL-6 are all non-specific mediators of inflammation; CRP is the most commonly used biomarker as a late-warning biomarker, whereas IL-6, an early-warning biomarker, has not been frequently employed in clinical settings because many hospitals do not have relevant detection capability. 14 15 Since the cut-off values for fecal calprotectin cannot be identified and it is significantly influenced by gestational and postnatal age, it is rarely used in routine clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there are various methods used to predict surgical NEC, among which inflammatory markers were more common because inflammatory mediators play a critical role in the occurrence of NEC. Early predictors that have been reported are as follows: C-reactive protein/albumin ratio, serum albumin concentration, interleukin (IL) 6 and coagulation function at NEC diagnosis, trends in C-reactive protein and lactate within 72 h of NEC diagnosis, IL-8 and IL-10 within 72 h of life (infants born less than 1500 g), and hyponatremia and/or the sudden decrease in plasma sodium at the onset of NEC (2,16,(31)(32)(33)(34). However, these methods have at least one of the following deficiencies, which limit clinical use and promotion: lack of enough sensitivity and specificity, expensive, inconvenience.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past several decades, selection of treatment strategies for NEC remains a challenge for pediatric surgeons and neonatologists. When inflammation and intestinal injury are limited, NEC can be treated medically, includes bowel rest and careful use of antibiotics, but surgery is needed if the patient continue to deteriorate after medical treatment or develop bowel perforation ( 2 ). Epidemiologic data revealed that about 30% of neonates with NEC may require surgical intervention with an overall case-fatality rate of 15% ( 3 ).…”
Section: Introductionmentioning
confidence: 99%